Pedagogic coordination: diversity going along with diversity (Research, Society and Development, 2019)
This work has the objective of presenting an experience report over an extracurricular period in Pedagogic Coordination activities, conducted on a public education institution in the country of Brazil, in the city of Natal/RN, with deaf students in the High School. Its characterized by being a descriptive study, Occurring over march/2018 until the end of the first semester of 2019. To communicate with the deaf students was used the Brazilian Sign Language (LIBRAS), recognized to be the second Brazilian official language by the Law nº 10.436, 24 April 2002. Studies involving sensorial deficiencies may indicate an easiest way to identify the necessities of learning and the use of necessary resources or support to the attendance of the deaf students. This way it’s understood that’s perceptible the necessity of another actions to a better learning of this persons, but it is observed that there is a lack of preparation on the initial/continued formation of those that compound the learning institution (since the persons who work on the entrances up to the teachers), in regarding of searching emergency solutions after this new demand installed on the school. The activities developed extracurricular period contributed to the built and upgrade of vision about the education on an inclusive perspective, and the importance of continued formation by an emancipatory and a critic form. Also permitted the articulation of the knowledge’s in Education with the daily of the involved people, in addition to the reflection around the importance of be felt included beyond the walls of the classroom.